PENGARUH BUDAYA ORGANISASI, PELATIHAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR BUPATI KABUPATEN KEPULAUAN MERANTI - Waluyo, Joko; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2015)
The purpose of this study was to determine the effect of Organizational Culture, Training and Motivation Employee Performance at Kantor Bupati Kabupaten Kepulauan Meranti. Research done at the Meranti Islands Regency Regency Office with research subjects were employees , the survey method used is the technique of multiple regression analysis . Samples were employees at Kantor Bupati Kabupaten Kepulauan Meranti, amounting to 75 people selected by simple random sampling technique . The instrument used to collect data is by using questionnaires . Validity was tested by using Product Moment formula and instrument reliability coefficients calculated using alpha Cronbach formula. The results showed that : ( 1 ) There is a positive effect of organizational culture , education and training and motivation on employee performance simultaneously at Kantor Bupati Kabupaten Kepulauan Meranti at Kantor Bupati Kabupaten Kepulauan Meranti. ( 2 ) There is a positive influence of organizational culture on the performance of partially at Kantor Bupati Kabupaten Kepulauan Meranti ( 3 ) There is a positive effect of education and training on employee performance partially at Kantor Bupati Kabupaten Kepulauan Meranti. ( 4 ) There is a positive effect of motivation on employee performance partially Regent Office Meranti Islands . To the staff at Kantor Bupati Kabupaten Kepulauan Meranti Regent advised to improve its performance as an effort to achieve organizational goals through education and training in order to improve their competence as an employee .Keywords : Performance , organizational culture , Education and Training and Motivation